ETHNOPEDAGOGY: INTEGRATING BUGIS LOCAL WISDOM INTO ISLAMIC EDUCATION TO FOSTER TOLERANCE AMONG PRIMARY SCHOOL STUDENTS - Andi Nurul Hafiza Darwis; Marhani Marhani; Bahtiar Bahtiar; Rustan Efendy (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimed to explore the integration of local wisdom into Islamic Religious Education (IRE) at SDN 43 Malino, focusing on how local Bugis values and Islamic teachings can foster tolerance among students. This study applied a qualitative approach with a case study research design. Using semi-structured interviews, participatory observation, and documentation to collect data from informants including the school principal, Islamic Education teachers, classroom teachers, and students. Findings indicated that integrating cultural values such as Mapatabe' (respect for parents), Gotong Royong (helping each other or working together), and Sipakatau' (mutual respect) shapes Islamic Religious Education (IRE) in teaching related to student tolerance. Activities such as communal prayers, Maulid celebrations, and traditional dances contribute to instilling values of respect and inclusivity. This study suggested that the integration of local culture with religious education plays an important role in shaping social behaviour and creating an inclusive and tolerant school environment. Cooperation between schools and parents was also crucial in supporting this educational approach, emphasising the importance of integrating local wisdom and ethnopedagogy into the educational framework to build tolerance and character in students. This research had implications for the development of more inclusive educational practices, highlighting the importance of ethnopedagogical methods in promoting social cohesion and tolerance in diverse educational environments.